PERBEDAAN HASIL BELAJAR MENGGUNAKAN MEDIA PERALATAN KANTOR DAN MEDIA GAMBAR - Devita Mandasari, Rijal Lubis2 (JURNAL PENDIDIKAN IPS, 2020)
The study examines the relationship between the application of internet media to the increase in social studies learning outcomes of class XI students of SMK Al-Washliyah 12 SeiRempah. The population in this study is less than 100, so that the entire population is used as a sample, that is, with a total of 50 students. The data analysis technique in this study uses the product moment correlation formula and the t test is used to test the hypothesis in the study. The results of this study found that the contribution of the application of internet media (X) to the increase in social studies learning outcomes (Y) was 0.515 or 51.5%. So from these calculations it can be seen that the contribution of the application of internet media (X) to the increase in IPS learning outcomes (Y) is 51.5%. while 48.5% are influenced by other variables. Hypothesis testing shows that the magnitude of tcount is 4.163, while the magnitude of ttable with a confidence level of 95% (level a = 0.05) and dk 50 - 2 = 39 is 2.012. Because t count> t table or 4,163> 2,012. From the results of these studies, the formulation of the hypotheses that have been determined in this study is acceptable, which means: "There is a significant influence between the use of the internet on social studies learning outcomes of XI graders of Al Washliyah Vocational School 12 SeiRempah Academic Year 2018-2019".